Exploring The Role of Decentered Orthokeratology Lenses in Controlling Myopia: A Longitudinal Study - Kumari, Sima; Tripathi, Himanshu; Taye, Trishna (Journal of Neonatal Surgery, 2025)
Purpose: This study aimed to evaluate the impact of orthokeratology (OK) lens decentration on myopia control, focusing specifically on its effect on axial length (AL) growth in children. We compared the outcomes of centrated versus decentered OK lenses over a 12-month period. Methods: In this retrospective study, 30 children (15 males, 15 females, mean age 9.3 ± 1.51 years) were included. Each child wore OK lenses with one eye fitted centrically and the other with decentered lenses for over 12 months. All participants had uncorrected visual acuity (UCVA) better than 0.1 logMAR and no significant ocular complications. We assessed refractive parameters, axial length growth, and myopia control efficiency, considering both the direction and degree of lens decentration. Results: The average decentration distance in the decentered group was 0.73 ± 0.25 mm. Axial length growth was significantly slower in the decentered group (0.20 ± 0.24 mm per year) compared to the centrated group (0.29 ± 0.20 mm per year) (p < 0.05). The efficiency of myopia control, determined by the ratio of AL growth between the decentered and centrated eyes, was 0.69 ± 0.50 for the temporal decentration group and 0.75 ± 0.52 for the other direction decentration group, showing no significant directional effect (p > 0.05). No significant correlation was observed between the degree of decentration and myopia control efficiency within the temporal decentration group. Conclusions: This study suggests that mild decentration of OK lenses may be more effective in slowing myopia progression than centration. There were no significant differences between temporal and other direction decentration, and no strong correlation between the degree of decentration and myopia control efficiency. These findings indicate that even modest lens decentration could be a promising strategy for myopia management in clinical practice..